2020
DOI: 10.1186/s12891-020-03569-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between clinical features and MRI findings in early adhesive capsulitis of the shoulder: a retrospective observational study

Abstract: Background: This retrospective study investigated the association between clinical features and MRI findings in patients with early adhesive capsulitis of the shoulder. Methods: The study included 29 patients with early adhesive capsulitis of the shoulder. The clinical diagnostic criteria were significantly restricted passive range of motion (ROM) and a symptom duration of up to 9 months. Various measurements related to adhesive capsulitis, including humeral and glenoid capsular thickness in the axillary reces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Inflammation and sequential fibrotic constriction of the periarticular and joint structures are potential causes of disability in adhesive capsulitis. Several reports demonstrated abnormalities in these structures in adhesive capsulitis, including thickening of the CHL, AR and RI, enhancement in the AR and obliteration of the fat triangle below the coracoid process in MRI analyses [ 7 , 19 , 20 ]. Ultrasound measurements also demonstrated a thickening of the RI, CHL, and AR in patients with adhesive capsulitis [ 4 , 8 , 9 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Inflammation and sequential fibrotic constriction of the periarticular and joint structures are potential causes of disability in adhesive capsulitis. Several reports demonstrated abnormalities in these structures in adhesive capsulitis, including thickening of the CHL, AR and RI, enhancement in the AR and obliteration of the fat triangle below the coracoid process in MRI analyses [ 7 , 19 , 20 ]. Ultrasound measurements also demonstrated a thickening of the RI, CHL, and AR in patients with adhesive capsulitis [ 4 , 8 , 9 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Hand et al [ 27 ] have shown that 41% of 223 patients had residual complaints during a follow-up of 2–20 years. Additionally, Kim et al [ 7 ] reported that 20.1% of 234 patients had residual shoulder pain and 39.7% of participants had persistent motion deficits after 2 years of follow-up. These discrepancies between studies could be the result of uncertainty of the pathophysiology and the natural course of adhesive capsulitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…66,67 The connection between calcitonin and FS was first noted when postmenopausal women being treated for osteoporosis with salmon calcitonin showed improvements in their FS symptoms. 68 Salmon calcitonin reduces TGFβ, type I collagen and type III collagen synthesis as well as fibroblast adhesion in cultured cells, 69 all of which are key mediators of fibrosis in FS. These results were confirmed in a double-blind, randomized, controlled trial in which intranasal calcitonin treatment improved shoulder pain and function faster than placebo in patients with FS.…”
Section: [H2] Metabolic Factorsmentioning
confidence: 99%